Ultrasonic motion detector - Abdul Hakim, Kassim (2008)
The ultrasonic motion detector is a project that using an ultrasonic sensor as it’s base to detect movement or moving object in small places. It is design to be a low cost ultrasonic motion detector. The transmitter sensor use to generate signal in that area. When the signal is block by moving or movement the receiver will gets the signal and amplifies the signal using transistor. The transistor is use as an amplifier to the receiver circuit. The Led and buzzer in the circuit use to see if there is movement detect by the sensor. The relay use to trigger another circuit when there is movement detects. The signal generate by the sensor is about ±40khz. This is a fully hardware design project plus it is built to be a portable ultrasonic motion detector.